Mali : Second and Third Reviews Under the Extended Credit Facility Arrangement. Requests for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Mali. (International Monetary Fund, 2021)
Against the background of the pandemic shock, a coup d'etat on August 18, 2020 led to a period of international disengagement with Mali and an economic blockade by ECOWAS until the appointment of a transitional government in October. Fund engagement was also put on hold during this period, delaying the resumption of discussions under the 2nd and 3rd reviews of the ECF. The transitional government, which will be in place for 18 months until general elections, announced its full adherence to the international obligations and commitments of the previous government, including the reform agenda under the ECF.